CAKRAWALA: A new pedagogical framework for enhancing literacy through creative problem-solving in project-based learning - Anita Dewi Utami; Ramdhan Fazrianto Suwarman; Intan Sari Rufiana; Sinta Agustin Ningseh; Djatmiko; Mat Rahimi Yusof (JPP (Jurnal Pendidikan dan Pembelajaran), 2025)
The "Design for Project Learning" instructional innovation integrates Design Thinking principles into Project-Based Learning (PjBL), enabling students to identify problems, develop creative solutions, present prototypes, and foster 21st-century skills. The objective is to design the "Design for Project Learning" model as a learning framework that prioritizes projects as the primary medium for learning, using Design Thinking principles to guide the development process. The methodology employed in this study is based on the educational problem-solving model developed by Plomp but limited to the first three phases. The findings from the initial investigation phase indicate the identification of instructional strategies by integrating PjBL syntax with the development steps of Design Thinking. Subsequently, in the design phase, the syntax for the "Design for Project Learning" instructional model was established, known as CAKRAWALA (CA: Causal Analysis, KRA: Knowledge Repository Approach, WA: Workflow Analysis, and LA: Luminous Appraisal). In the realization phase, validation of the "Design for Project Learning" syntax was conducted, involving experts in instructional material, instructional design, and pedagogy. Based on the research findings, the "Design for Project Learning" instructional model has been validated and can be implemented, as well as tested in future studies to further refine the instructional design, potentially leading to the development of a new instructional model.